2019
DOI: 10.1029/2019je005949
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Endeavour Crater Based on Orbital and Rover‐Based Observations in Combination With Landscape Evolution Modeling

Abstract: Exploration of Endeavour crater's Shoemaker formation rim rocks by the Opportunity rover, combined with extensive observations from the Mars Express and Mars Reconnaissance Orbiters, provides unique and quantitative insights into the processes that have degraded this 22‐km diameter Noachian age impact crater. These insights are informed by comparisons between Endeavour and the relatively young, and morphologically fresh appearing, 19‐km diameter Bopolu crater located 65 km to the southwest. Analyses of rover a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Endeavour crater is Noachian in age, and thus, the upper Shoemaker unit might also be part of the subdued cratered unit. The degradation of Endeavour crater rim took place when surface waters were actively modifying surface morphology (Hughes et al., 2019), which is characteristic of the subdued crater unit (Hynek & Di Achille, 2017). However, the differences in alteration styles recorded in the upper Shoemaker versus lower Shoemaker and Matijevic formation indicate that the former was deposited after a substantial time gap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endeavour crater is Noachian in age, and thus, the upper Shoemaker unit might also be part of the subdued cratered unit. The degradation of Endeavour crater rim took place when surface waters were actively modifying surface morphology (Hughes et al., 2019), which is characteristic of the subdued crater unit (Hynek & Di Achille, 2017). However, the differences in alteration styles recorded in the upper Shoemaker versus lower Shoemaker and Matijevic formation indicate that the former was deposited after a substantial time gap.…”
Section: Discussionmentioning
confidence: 99%
“…Grant et al. (2016) concluded that the Endeavour rim was degraded in part by fluvial processes and this is also indicated by modeling of Endeavour crater degradation (Hughes et al., 2019). Fluvial erosional and depositional processes were important in modifying subdued cratered unit surfaces, but not on the overlying Noachian cratered unit (Hynek & Di Achille, 2017).…”
Section: Nature Of the Subdued Cratered Unitmentioning
confidence: 94%
See 1 more Smart Citation
“…The topographic relief associated with the morphodynamic preservation of channel belts is present, and even exaggerated, in subaqueous settings (Jobe et al, 2020) and perhaps even across planets. Fluvial channel belts exposed at the surface of Mars can be mapped for 10s and even 100s of km (Davis et al, 2019;Hughes et al, 2019;Williams et al, 2013), likely due to the extent of their initial preservation followed by the relative gentleness of their exhumation (Burr et al, 2009;. In outcrops at Aeolis Dorsa, Mars, with depositional settings interpreted as coastal, stacking and shingling at the channel belt and lobe scales are common DiBiase et al, 2013;Hughes et al, 2019).…”
Section: Morphodynamic Preservation Of Fluvial Channel Beltsmentioning
confidence: 99%
“…Fluvial channel belts exposed at the surface of Mars can be mapped for 10s and even 100s of km (Davis et al, 2019;Hughes et al, 2019;Williams et al, 2013), likely due to the extent of their initial preservation followed by the relative gentleness of their exhumation (Burr et al, 2009;. In outcrops at Aeolis Dorsa, Mars, with depositional settings interpreted as coastal, stacking and shingling at the channel belt and lobe scales are common DiBiase et al, 2013;Hughes et al, 2019). In the Hellas basin on Mars, exposures may have an architecture more consistent with reworking, with highly amalgamated fluvial strata (Salese et al, 2020).…”
Section: Morphodynamic Preservation Of Fluvial Channel Beltsmentioning
confidence: 99%